Raise a Glass to the Season! : CASE-MCQ Invites You to an Evening of Stories, Music and Conversation with Rob Lutes - Centre for Access to Services in English (CASE) (2020)

End of the Year Recipe Exchange : 2020-2021 - Centre for Access to Services in English (CASE) (2020)

Partners in Health - Centre for Access to Services in English (CASE) (2020)

$40,000 Awarded in Student Leadership Bursaries for the Mauricie/Centre-du-Québec Region - Miller, Julie; Vidal, Emily (2020)

Fall Colours Acoustic Concert - Cancelled Due to COVID-19 - Centre for Access to Services in English (CASE) (2020)

Case Welcomes Three New Employees - Centre for Access to Services in English (CASE) (2020)

Partners in Health - Centre for Access to Services in English (CASE) (2020)

Caregivers' Guide : Local and Regional Resources for Caregivers in the Centre-du-Québec - Centre for Access to Services in English (CASE) (2020)
The Institut de la Statistique du Québec states that as of 2015 as many as a quarter of the population of Québec were caregivers, the majority being female, for people with long-term health complications. The recipient of the care is most often a family member. The reason for needing care varies between chronic illness, disability, and difficulties related to aging. Of those providing care to family members, greater than one third act as a caregiver to more than one person.

Partners in Health - Centre for Access to Services in English (CASE) (2020)

Partners in Health - Centre for Access to Services in English (CASE) (2020)

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)